2018
DOI: 10.1103/physreva.98.043427
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of Xe and Xe@C60 from the 4d shell in RABBITT fields

Abstract: We consider photoemission from the 4d shell of the free Xe and encapsulated Xe@C 60 atoms by ionizing XUV and probing IR fields typical for a RABBITT (reconstruction of attosecond beating by interference of twophoton transitions) measurement. Our theoretical model is based on the numerical solution of the time-dependent Schrödinger equation in the single-active-electron approximation. The fullerene C 60 cage is represented by a finite-width well potential. We test our model against an analogous set of nonrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Here the valence np shell ionization leads to the competing s and d partial waves and the Wigner time delay becomes angular dependent. This effect was predicted theoretically in Ne (Ivanov and Kheifets 2017) and heavier noble gases (Bray et al 2018a(Bray et al , 2018b). An illustration of this effect is presented in figure 13.…”
Section: Angle Resolutionsupporting
confidence: 63%
“…Here the valence np shell ionization leads to the competing s and d partial waves and the Wigner time delay becomes angular dependent. This effect was predicted theoretically in Ne (Ivanov and Kheifets 2017) and heavier noble gases (Bray et al 2018a(Bray et al , 2018b). An illustration of this effect is presented in figure 13.…”
Section: Angle Resolutionsupporting
confidence: 63%
“…There has been significant theoretical work on the angle-dependent time delay, for example, Refs. [26][27][28][29][30][31][32], but fewer related experimental reports [12,28,33], all using the RABBITT technique. The Wigner delay is theoretically isotropic for single-photon ionization of He, but Heuser et al [28] observed an angular dependence in photoemission delay, attributed to the XUV þ IR two-photon ionization process, inherent in RABBITT interferometry.…”
Section: Introductionmentioning
confidence: 99%
“…contains an effective one-electron potential V (r) (Kr [21], Xe [20]). The HamiltonianĤ int (t) describes interaction with the external field and is written in the velocity gaugê…”
Section: A One-electron Tdse and Hhg Spectrummentioning
confidence: 99%
“…As previously [19,20], we solve the one-electron TDSE for a target atom i∂Ψ(r, t)/∂t = Ĥatom + Ĥint (t) Ψ(r, t) ,…”
Section: A One-electron Tdse and Hhg Spectrummentioning
confidence: 99%